2003
DOI: 10.1002/pssc.200303346
|View full text |Cite
|
Sign up to set email alerts
|

Increase in luminescence efficiency of GaPN layers by thermal annealing

Abstract: The effect of rapid thermal annealing (RTA) on the luminescence properties of GaPN layers was investigated. GaPN layers were grown on GaP and Si substrates. The luminescence properties were evaluated by cathodeluminescence and low-temperature photoluminescence. It was found that the luminescence intensity was increased and the peak photon energy was shifted to the high-energy side in all samples after RTA. The luminescence intensity of the GaPN layers was increased with increasing the annealing temperature. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 8 publications
1
26
0
Order By: Relevance
“…In case of OMVPE-grown sample, integrated PL intensity became about 20 times strong by the annealing. The improvement of PL intensity is observed for MBE-grown samples [7], but the effect is much larger in OMVPE grown samples than the MBE grown one. PL peak shape and the peak energy of the OMVPE-grown sample did not change by the annealing, which is quite different from the results of MBE-samples, i.e., PL intensity at lower energy tail decreased by the annealing, and higher energy side became strong.…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…In case of OMVPE-grown sample, integrated PL intensity became about 20 times strong by the annealing. The improvement of PL intensity is observed for MBE-grown samples [7], but the effect is much larger in OMVPE grown samples than the MBE grown one. PL peak shape and the peak energy of the OMVPE-grown sample did not change by the annealing, which is quite different from the results of MBE-samples, i.e., PL intensity at lower energy tail decreased by the annealing, and higher energy side became strong.…”
Section: Resultsmentioning
confidence: 79%
“…For the MBE grown samples, the effects of post growth annealing on PL properties are believed a reduction of spatial fluctuation of nitrogen compositions and the density of defects attributed to nitrogen atoms, and the blue-shift could be caused by the improvement of the uniformity of the nitrogen compositions and the increase in injected carriers due to the decrease in defects [7]. The small blue-shift observed in OMVPE sample suggests that the spatial fluctuation of nitrogen compositions is smaller than the MBE samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the same tendency has not been seen in carbon doped GaPN. Second, the annealing process at 900 °C for 1 min does not influence on n h and μ h , although it has been reported that the same annealing process significantly improves crystallinity and intensifies photoluminescence in undoped and Mg-doped ptype GaPN epilayers [10,11]. Figure 4 shows PL spectra of GaP and GaPN measured at 10 K. Both in GaP and GaPN, the carbon incorporation reduces the PL intensity without peak shift, and the peak intensity decreases with the increase of n h .…”
Section: Resultsmentioning
confidence: 97%
“…Prior to the growth of C-doped GaP and GaPN layers, a 100-nm-thick undoped GaP buffer layer was deposited. A rapid thermal annealing (RTA) at 900 ºC for 60 s under a flow of N 2 gas was performed for carbon doped samples, as it has been reported that the same RTA process is significantly effective in improving crystallinity and intensifying PL in undoped and Mg-doped p-type GaPN films [5].…”
Section: Methodsmentioning
confidence: 99%